Intercultural Communication in English for Business - Muthia Mutmainna Darmuh; Mujib Hasib (Generasi Sains Indonesia, 2024)
This paper discusses how intercultural competence can be incorporated into the English as a business instruction in Indonesia, where the current methods of teaching still put a great emphasis on grammar and language accuracy. The research, qualitative and based on literature, resorts to sociocultural and sociolinguistic theories to examine the way in which language should be viewed not only as a communicative means, but also as a means of cultural negotiation. The findings confirm three major observations: first, the current curricula lacks sufficient coverage of cultural aspects of communication; second, experiential techniques of learning (role plays and case studies) are necessary to develop the ability to change and be interculturally sensitive; and third, institutional and policy-level support is necessary to maintain a significant change. One of the conclusions of the study is that linguistic proficiency cannot on its own guarantee success in global business situations. Rather, intercultural competence, defined as capacity to decode cultural messages, cope with uncertainty, and relate ethically to divergent thinking, should be made the core of business English teaching in Indonesia.